LARGE-SCALE COLONISATION OF THE SPAT OF MUSSEL, MYTILUS VIRIDIS, IN COCHIN REGION - Nair, R V; Nayar, K Nagappan; Mahadevan, S (Indian Journal of Fisheries, 2011)
Large-scale colonisation of the spat of the green mussel, Mytilus viridis, a species heretofore considered as not existing in sizable quantities in the Cochin region, was noticed on the anti-erosicm granitestone embankments of Andakaran Azhi beach between Shertalai and Cochin. The spat, which appear to settle during the postfflonsoon period, grow in profusion in the midlittoral and infralittoral regions. The density of the population varies from surface to surface even on a single boulder. A marked concentration is noticed in the sheltered, dark niches beneath the stores, while the flat upper surfaces that are constantly exposed to severe wave actions appear to be least suitable for mussel growth. It was estimated that on an average, 220-248 spat|100 Cm’ were in areas submerged most of the time, while 112-170, in less favourable surroundings. The population which is densest at Andakaran Azhi diminishes gradually northwards. But on the whole, the potentiality of this resource is large enough to provide ample seed for extensive culture operations along this region